Stent-assisted coiling vs. coiling alone of ruptured tiny intracranial aneurysms: A contemporary cohort study in a high-volume center - Zhang, Guanghao; Wu, Yina; Wei, Yanpeng; Xue, Gaici; Chen, Rundong; Lv, Nan; Zhang, Xiaoxi; Duan, Guoli; Yu, Ying; Li, Qiang; Xu, Yi; Huang, Qinghai; et al. (Frontiers in Neurology, 2022)
Objective: To compare the safety and efficacy of stent-assisted coiling with those of coiling alone for the treatment of ruptured tiny intracranial aneurysms. Methods: We enrolled 245 patients with ruptured tiny intracranial aneurysms treated with coil embolization. Patients were grouped into stent-assisted coiling and coiling alone groups. Baseline characteristics, periprocedural complications, clinical outcomes, and angiographic results were compared between the two groups. In addition, a subgroup analysis was conducted in the stent-assisted coiling group, and patients were regrouped into LVIS and laser-cut groups to compare the perioperative procedure-related complications and clinical and angiographic follow-up outcomes. Results: All baseline characteristics were equivalent between the two groups except for aneurysm size and dome-to-neck aspect ratio. The rates of overall procedure-related complications, intraprocedural rupture, postoperative early rebleeding, intraprocedural thrombosis, postprocedural thrombosis and procedure-related mortality were comparable between the two groups (P=0.105, 0.145, 0.308, 1.000, 1.000, 0.160, respectively). Nevertheless, the rate of hemorrhagic complication in the SAC group were significantly higher (P = 0.023). The angiographic follow-up outcomes showed that the SAC group had a higher complete occlusion rate and lower recurrence rate (88.2% vs 67.1%, 5.4% vs 15.2%, P = 0.001). The clinical outcomes at discharge and follow-up between the two groups demonstrated no significant differences (P = 0.192 and P = 0.085, respectively). For subgroup analysis, LVIS stents were associated with a signiﬁcantly higher rate of complete occlusion (P=0.014) and a lower rate of intraprocedural rupture (p = 0.021). Moreover, multivariate analysis showed that there were no predictors for the overall, hemorrhagic and ischemic procedure-related complications, while Raymond class was an independent predictor of retreatment (OR = 3.508, 95% CI 1.168–11.603; P = 0.029). Conclusions: Stent-assisted coiling of selected aneurysms can be performed with favorable angiographic and without additional neurologic impairment when compared to stand-alone coiling. Sub-group analyses showed that both LVIS and laser-cut stent were safe and effective with satisfactory angiographic and clinical results. However, laser-cut stent treatment is associated with statistically signiﬁcant higher intraprocedural rupture risk. Prospective studies with larger sample sizes are needed to further confirm the safety and efficacy of the stent-assisted coiling strategy.